Analisis Struktur Kristal dan Sifat Kemagnetan Material Komposit Perovskite Manganit Nd0,6Sr0,4MnO3/ZnO - Muhammad Umar Faruqi; Arif Tjahjono; Sitti Ahmiatri Saptari (Al-Fiziya: Journal of Materials Science, Geophysics, Instrumentation and Theoretical Physics, 2020)
AbstrakPerovskite manganit merupakan salah satu rekayasa material yang dapat menghasilkan perubahan fenomena fisika. Telah berhasil dibuat material berbasis perovskite manganit Nd0,6Sr0,4MnO3 menggunakan metode sol-gel¬ dan dikompositkan dengan ZnO (Nd0,6Sr0,4MnO3)1-x/(ZnO)x (x = 0; 0,3; 0,5; 0,7). Hasil pengujian X-Ray Diffraction menunjukkan sampel Nd0,6Sr0,4MnO3 berstruktur tunggal ortorombik dan sampel ZnO pada (Nd0,6Sr0,4MnO3)0,5/(ZnO)0,5 berstruktur heksagonal tunggal. Hasil pengujian Field Emission Scanning Electron Microscope menunjukkan sampel telah homogen dengan rata-rata ukuran butir 0,188 μm. Hasil pengujian Vibrating Sample Magnetometer menunjukkan sampel (Nd0,6Sr0,4MnO3)0,5/(ZnO)0,5 bersifat paramagnetik dan mengalami penurunan sifat magnetik juga suseptibilitas seiring dengan penambahan konsentrasi material ZnO. AbstractPerovskite manganite is one of the manipulation materials that can produce changes in physical phenomena. Perovskite material Nd0,6Sr0,4MnO3 has been made with the sol-gel method and then composites with ZnO (Nd0.6Sr0.4MnO3)1-x/(ZnO)x (x = 0; 0.3; 0.5, 0, 7). The results of the X-Ray Diffraction characterization test showed samples of Nd0,6Sr0,4MnO3 and ZnO each with a single orthorhombic phase with a Pnma space group and a single hexagonal with a P63mc space group. The results of the Field Emission Scanning Electron Microscope characterization test showed that the samples were homogeneous with an average grain size of 0,188 μm. Vibrating Sample Magnetometer characterization test results show composite material (Nd0,6Sr0,4MnO3)1-x/(ZnO)x are paramagnetic and the increasing composition of ZnO material decreases the magnetization and susceptibility value of sample